Continuum of Violence: Concentration Camps in Kenya - Popławski, Błażej (Instytut Historii PAN, 2024)
The purpose of the article is to discuss the concentration camps established by the British in the Colony and Protectorate of Kenya in 1952–60 and by Kenyan authorities in North Eastern Province in 1963–67. Reconstructed is the system of camps established for the purpose of incarcerating the Mau Mau rebels. Also discussed are actions taken by the authorities in independent Kenya toward the Somali minority during the so-called Shifta War.
p. 119-140
Summary in English and Polish
Keywords: Africa; Kenya; concentration camps; Mau Mau; Kikuyu; Somalis; Shifta War